ABOUT OIL AND GAS OCCURRENCES OF STRATOSPHERIC SUPERDEEP OBJECTS - M. Z. Rachinsky (Известия высших учебных заведений: Геология и разведка, 2018)
Based on the analysis and synthesis of the resent factual data and topic-based materials, polygenous (organic and mantle) nature of hydrocarbon generation in the super-deep petroleum basins sedimentary sections at depth intervals of 8 to 12 km has been substantiated. A hydrocarbon generation and accumulation concept in natural reservoirs under the dispersed organic matter thermocatalysis model at depth interval of 3 to 5 km and invasion of the mantle fluids in geological objects at depths of 8 to 12 km and more has been proposed.